Functional-economic diagnostics of hr management in construction enterprises: structural, process, and methodological-analytical components - Omelianenko , Maryna (Ways to Improve Construction Efficiency, 2024)
The article explores modern economic and managerial components that ensure effective HR management in construction enterprises, with a focus on the strategic transformations of the industry. It examines the genesis of key theoretical approaches to personnel management, based on the works of foundational thinkers such as Frederick Taylor, Elton Mayo, Abraham Maslow, and Peter Drucker. Contemporary studies are analyzed, highlighting the implementation of flexible methodologies, digital technologies, business process reengineering, and organizational culture development. Key indicators for assessing HR management systems in the construction sector are identified, combining quantitative (productivity, adherence to deadlines) and qualitative metrics (motivation, engagement). The study analyzes HR management systems in various countries, reflecting their cultural, economic, and social characteristics. It is determined that the U.S. emphasizes productivity and motivation through bonuses; Japan focuses on collectivism and loyalty; Germany stands out for its structured approach and technical competence; France prioritizes social protection, while the UK exhibits adaptability. China and India highlight hierarchy, whereas Sweden and Australia emphasize equality and innovation. These differences underscore the necessity of adapting HR strategies to local contexts. Particular attention is paid to the changing hierarchy of HR management tasks within the strategic transformation field. The main directions include developing personnel strategies, fostering a culture of change, integrating innovative solutions and digital technologies, and enhancing motivation and feedback programs. The importance of avoiding destructive phenomena through transparent evaluation mechanisms, fair criteria, and adherence to ethical standards is emphasized. The article summarizes best practices and provides recommendations to enhance HR management effectiveness in construction enterprises, focusing on integrating traditional and modern approaches into strategic management. The presented material is valuable for researchers, practitioners, and managers aiming to optimize HR processes and ensure long-term development in the construction sector.